Analisis Pengembangan Potensi Ekonomi Desa Dalam Meningkatkan Kesejahteraan Melalui Badan Usaha Milik Desa (BUMDes) di Desa Kisam Lestari Kec. Lawe Sumur Kab. Aceh Tenggara - Cahaya, Nilam; Harmain, Hendra; Ilhamy Nasution, Muhammad Lathief (Universitas Labuhanbatu, 2023)
This study aims to analyze the development of village economic potential through village-owned enterprises (BUMDes) in Kisam Lestari Village, Kec. Lawe Sumur District. Southeast Aceh. This research method is qualitative research. The subjects in this study were the village head, the head of BUMDes, and 3 communities. Data collection techniques with observation, interviews and documentation. The results revealed that the existence of BUMDes can improve the community's economy. The process and efforts of community economic development through BUMDes consist of trading business units and service business units. Both business units can help increase the income of the people of Kisam Lestari village. The funds collected through BUMDes are put into the village Treasury which is reused by the village and the funds can be allocated for the needs of the community physically and non-physically. For the next researcher, it is expected to further develop this research well when conducting research that is still related to the analysis of the development of village economic potential through village-owned enterprises (BUMDes).Â